Southern black widow Latrodectus mactans (Fabricius) (Arachnida: Araneae: Theridiidae) - Amanda Eiden; Phillip E. Kaufman (EDIS)
The Southern black widow spider, Latrodectus mactans (Fabricius), is a venomous spider found throughout the southeastern United States. Widow spiders received their name from the belief that they would kill and consume their mate following copulation. However, the practice was mainly observed in laboratory settings under crowded conditions. It is believed that sexual cannibalism within the widow species in natural settings is more associated with the male’s physical inability to escape rather than the female’s interest in consuming him. This 6-page fact sheet was written by Amanda Eiden and Phil E. Kaufman and published by the UF Department of Entomology and Nematology, May 2013.